Derogating benevolent behavior of deviant in-group members: group processes within a real-life sample of heterosexual Christians. (2nd January 2016) - Cramwinckel, Florien M.; van den Bos, Kees; van Dijk, Eric; Schut, Marijke
Abstract: How do people evaluate potentially good and desirable behavior by others? We investigate how participants ( N  = 154) evaluate a couple that wants to adopt an orphan that would otherwise die. We collected data from heterosexual Christians in two cities in the Dutch Bible belt. We manipulated whether the adoptive-parents-to-be were a heterosexual couple or a lesbian couple and whether the couple self-identified as devout Christians or not. Using a subjective group dynamics account, we predicted and found that participants evaluated the lesbian couple in more negative terms than the heterosexual couple, especially when this couple was also Christian. These findings illustrate how positive behavior is derogated when displayed by in-group deviants.